العمل الانفعالي وعلاقته بالأداء العلمي لدى معلمي الجامعة - احمد, سارة ابراهيم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The research is based on the theory of emotional events and explores the relationship between emotional labor and the performance of university professors. Relevant data were obtained through a questionnaire. The research objectives are: - To identify emotional labor among university professors, their job performance, and their relationship to emotional labor and job performance. The research sample consists of (100) professors. The research reached the following results: There is a good level of emotional labor among university professors, a good level of job performance among university professors, and a statistically significant relationship between emotional labor and its relationship to job performance among university professors.